Chapter 2 - Path - J-A. van den Berg (Acta Theologica)
From text: In the act of embarking on the path towards design and construction, movement is architectonically embodied, in the sense that “the path is that which we follow” (Norberg-Schulz 2000:144). A stop is made at the first station, namely that of the gallery, for the purpose of exploring the different research paths that have been made possible by, inter alia, practical theology and futures studies.